Neurosurgery in COVID-19 Ground Zero: The Weill Cornell Medicine Experience - Winston, Graham M. (World Neurosurg, 2021)
The mobilization of subspecialty departments in reaction to the unique demands of the onset of the coronavirus disease 2019 (COVID-19) pandemic in New York City was swift and left little time for reflection and commemoration. The early days of the pandemic brought unprecedented stressors on the medical system that necessitated a restructuring of hospitals, reallocation of health care workers, and a shift in care and education paradigms to meet patient care demands and public health needs. As the number of cases, intensive care unit patients, and deaths skyrocketed in New York City, many struggled with a somewhat paradoxical difficulty in perceiving the human value of what these numbers mean. Easily lost in the statistics are the stories and experiences of the physicians and trainees who were counted on to halt their own clinical practices and adapt their skillsets to tackle the pandemic. In this article, we present 10 brief narratives from the student members of the Neurosurgery Publication Group at Weill Cornell Medical College and members of the Weill Cornell Medicine Neurological Surgery Residency Program and Department of Neurological Surgery faculty. Reflecting on these individual experiences gives us an opportunity to simultaneously contribute to a history of New York City's reaction to COVID-19 and commemorate the individuals who were impacted by or succumbed to this disease.